.93x+.97(4-x)=3.8

Simple and best practice solution for .93x+.97(4-x)=3.8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .93x+.97(4-x)=3.8 equation:


Simplifying
0.93x + 0.97(4 + -1x) = 3.8
0.93x + (4 * 0.97 + -1x * 0.97) = 3.8
0.93x + (3.88 + -0.97x) = 3.8

Reorder the terms:
3.88 + 0.93x + -0.97x = 3.8

Combine like terms: 0.93x + -0.97x = -0.04x
3.88 + -0.04x = 3.8

Solving
3.88 + -0.04x = 3.8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3.88' to each side of the equation.
3.88 + -3.88 + -0.04x = 3.8 + -3.88

Combine like terms: 3.88 + -3.88 = 0.00
0.00 + -0.04x = 3.8 + -3.88
-0.04x = 3.8 + -3.88

Combine like terms: 3.8 + -3.88 = -0.08
-0.04x = -0.08

Divide each side by '-0.04'.
x = 2

Simplifying
x = 2

See similar equations:

| 2(x-4)-x=3 | | (3x-3)(3x-8)= | | 1+8(-4n-2)=-39-8n | | -2/3r+2r=6/5r+12/5 | | (4x^2+1)(6x^2+7)= | | 5x-6-2x=4x+8 | | 6x+6=6x-9 | | 2/3(6x+9)=18 | | -8v=-80 | | -2(-x-8)=2x+15 | | -3(x-5)+12x=9(x+2)+12 | | 60+15=4 | | d-16=-50 | | 2(6w+8)=2(4w+24) | | (3x+5)=2(x+7) | | -6(x-8)=48 | | n+t+g+h=106 | | 162=11x+19 | | 3(x+5)+4x=-(x-5) | | x-1=-4*1 | | 34+4k=102 | | 15=3xy-1 | | 0.75n-3=-9 | | 2/3+4=8 | | 64=4v | | M=1/k+n | | W=x-y/2 | | 3x-8x-4=8x | | j/6-9=5/9 | | x-27=43 | | (x-3/5)^2+y^2-9=0 | | 27.3m-45.1=-13.2+6.8 |

Equations solver categories